2016
DOI: 10.1002/jsfa.7976
|View full text |Cite
|
Sign up to set email alerts
|

Microwave thawing and green tea extract efficiency for the formation of acrylamide throughout the production process of chicken burgers and chicken nuggets

Abstract: When the AA levels of commercial CBs and CNs are compared with those produced in our experiment, the use of green tea extract could be a novel, easy and practical application for fast food producers to minimise AA levels in the first two steps of the production without changes to the sensory properties of the final products. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…The degree of the acrylamide reduction by phenolic compounds showed a close correlation between the number of phenolic hydroxyls instead of alcoholic hydroxyls in different types of flavonoids. Soncu and Kolsarici [ 100 ] also attributed a beneficial effect of phenolic compounds in reducing AA content, recommending the addition of green tea extracts containing large amounts of these compounds to poultry products. They claim that the radical-trapping effect of catechins or inhibition of the Maillard reaction by catechins present in green tea could be considered a possible explanation for the reduction of acrylamide formation.…”
Section: Acrylamide In Microwave Heatingmentioning
confidence: 99%
“…The degree of the acrylamide reduction by phenolic compounds showed a close correlation between the number of phenolic hydroxyls instead of alcoholic hydroxyls in different types of flavonoids. Soncu and Kolsarici [ 100 ] also attributed a beneficial effect of phenolic compounds in reducing AA content, recommending the addition of green tea extracts containing large amounts of these compounds to poultry products. They claim that the radical-trapping effect of catechins or inhibition of the Maillard reaction by catechins present in green tea could be considered a possible explanation for the reduction of acrylamide formation.…”
Section: Acrylamide In Microwave Heatingmentioning
confidence: 99%
“…found that p ‐Coumaric acid strongly inhibited AA formation during the Maillard reaction, and the inhibitory rate was up to 82.69% in the chemical model systems and 66.2% in fried potato chips. Soncu & Kolsarici ()AUTHOR: Soncu et al . (2016) has been changed to Soncu and Kolsarici (2016) so that this citation matches the Reference List.…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez-Zapata et al (2010) also obtained similar results while producing burgers containing added tiger nut fibers. The compounds that impart a characteristic color to heat-treated products are produced because of the Maillard reaction, owing to the caramelization of carbohydrates, and the oxidation of fats (Sánchez-Zapata et al, 2010;Soncu & Kolsarici, 2016). Heat treatment reduced the effects of flour addition on the colorimetric profile, which is an advantageous factor, considering that the product would be consumed after cooking.…”
Section: Visual Appearance and Colorimetric Profilementioning
confidence: 99%